Exploring the role of domestic and foreign factors in Indonesian Islamic mutual funds - Muhammad Adnan (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2023)
Purpose — This study aims to test and analyze domestic and foreign factors' effects on Islamic mutual funds' long-term and short-term Net Asset Value in Indonesia.Method — The research is associative quantitative research. The data used is secondary data in the form of time series data for 2015-2022. Data sources were obtained from the Central Bank of Indonesia, the Financial Services Authority, and Yahoo Finance. Data analysis used time series econometrics with the Error Correction Model (ECM) approach.Result — The ECM estimation results show that in the long run, the money supply, the Jakarta Composite Index (JCI), positively affects the Net Asset Value (NAV) of Islamic mutual funds, and World oil prices hurt the NAV of Islamic mutual funds in Indonesia. In contrast, the World gold price does not affect the NAV of Islamic mutual funds. In the short term, JCI positively affects the NAV of Islamic mutual funds, and the World gold price hurts the NAV of Islamic mutual funds in Indonesia. Conversely, money supply and World oil prices do not affect the NAV of Islamic mutual funds in Indonesia.Contribution — This study makes a significant academic contribution by expanding the understanding of factors influencing the Net Asset Value (NAV) of Islamic mutual funds in Indonesia, addressing the research gap regarding the limited inclusion of variables, and suggesting the need for further exploration and comparative studies in different countries or regions.